2021
DOI: 10.3390/bios11090318
|View full text |Cite
|
Sign up to set email alerts
|

Objectively Measured Physical Activity in Patients with Coronary Artery Disease: A Cross-Validation Study

Abstract: Physical activity (PA) and sedentary behavior (SB) levels in healthy adults are predominately based on self-reporting measures, which generally overestimate PA but underestimate SB. Patients with coronary artery disease (CAD) eligible for cardiac rehabilitation (CR) follow an individualized program; thus, objective assessment of physical performance and regular daily activity is required. This study aimed to compare self-reported and objectively measured PA and SB in patients with CAD prior to out-patient CR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
3
10
1
Order By: Relevance
“…Answers were compared with the objectively assessed moderate and vigorous physical activity analysed by cut-off points of a highly accurate diagnostic instrument, the accelerometer, as a reference standard (Innerd, 2020). Our results are similar to a systematic review about physical activity questionnaires and accelerometery that showed weak to moderate correlations (Skender et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Answers were compared with the objectively assessed moderate and vigorous physical activity analysed by cut-off points of a highly accurate diagnostic instrument, the accelerometer, as a reference standard (Innerd, 2020). Our results are similar to a systematic review about physical activity questionnaires and accelerometery that showed weak to moderate correlations (Skender et al, 2016).…”
Section: Discussionsupporting
confidence: 61%
“…The level of physical activity and adherence to physical activity guidelines among out-of-hospital cardiac arrest (OHCA) survivors is unknown (Ambrosetti et al, 2020;Bull et al, 2020;Visseren et al, 2021). While objective measures are often considered as reference standard for assessment of physical activity (Innerd, 2020), selfreports are often the only feasible method in many settings. In the large international Targeted Hypothermia versus Targeted Normothermia after Out-of-Hospital Cardiac Arrest (TTM2) trial, two questions for self-reported physical activity were included as a part of the cardiovascular risk assessment, based on the recommendations for primary and secondary prevention (Lilja et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the patients’ physical activity was subjectively assessed using the short form of the International Physical Activity Questionnaire, which was recently shown to overestimate physical activity and underestimate sedentary behavior compared with accelerometry in patients with coronary artery disease . The same discrepancies between objectively and subjectively assessed physical activity have also been shown in patients with PAD .…”
supporting
confidence: 65%
“…On the other hand, both physical activity and the decrease of sedentary behaviors could reduce several comorbidities. Therefore, the use of technologies and devices focused on increasing physical activity could improve wellbeing [ 28 , 29 ]. In our study, half of the participants (44.6% of men and 50% of women) were not interested in receiving continuing advice about cardiac rehabilitation in their mobile phone or Smartphone, primarily because of concerns about their data privacy after registering in the virtual applications or games.…”
Section: Discussionmentioning
confidence: 99%